EFIKASI INSEKTISIDA NABATI DALAM MENGENDALIKAN KUTU KEBUL, Bemisia tabaci GENN. (HOMOPTERA: ALEYRODIDAE) - Kurnia Paramita Sari; Suharsono Suharsono (Widyariset, 2014)
Yam bean, neem, and nicotiana are natural pesticides for insect. Whitefly Bemisia tabaci Genn. is a pest and could decrease in soybean yield up to 80%. The aim of this research was to study the effectiveness of natural pesticides in controlling white fly. The research was carried out in ILETRI screen house and arranged in a 3 x 3 factorial randomized design with four replicates. Fisrt factor was three natural pesticides of yam bean, neem, nicotiana while the second factor was the time of aplications (two week after planting (WAP)-harvested), (2 WAP- floweres), (floweres-harvested). Dosage of each yam bean, neem or nicotin was 50 ml/l. Natural pesticides were sprayed over leaves. Parameters of whitefly population and injury intensity were observed. The result showed that whitefly population was lower in neem aplication (113 whitefly/3 leave trifoliate) and increased in control (684 whitefly/3 leave trifoliate), yam bean aplication (182 whitefly/3 leave trifoliate ) and nicotiana aplication (163 whitefly/3 leave trifoliate ). There was not interaction the kind of natural pesticides with time of application. This study shown that the neem natural pasticide at 2 WAP until harvest is effective in controlling the whitefly.